ANALISIS PENDIDIKAN AKHLAK BAGI ANAK PERSPEKTIF SYEKH MUSTHAFA AL-GHALAYAINI DALAM KITAB ‘IZHAH AL-NASYI’IN - Ulva Badi’ Rohmawati; Sitti Atiyatul Mahfudoh (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2022)
Moral decadence is one of things that is getting very serious attention today. Mainly moral decadence in adolescents. Hedonic lifestyle, free sex, alcoholic beverages, pornography, game addiction, and so on. The development of an increasingly modern era, with increasingly rapid technological sophistication, also has an impact on human behavior. Teenagers are most vulnerable to being affected because they are still in the stage of searching for identity.High curiosity, the desire to try new things, make them always interested in knowing new things that they have not known before. The sophistication of technology and an increasingly modern life style society sometimes makes teenagers missunderstanding that their actions are wrong. Therefore, it is very important to introduce, teach, and set an example for teenagers on how good morals and behavior should be. In the book of Izhah Al-Nasyi'in, Sheikh Mustafa Al-Ghalayaini has a good concept of moral education for teenagers. According to him, education is instilling the main character, noble character and great education in the souls of teenagers and watering them with useful instructions and advices, becoming traits that are embedded in the soul. So that the fruit appears in the form of the main deeds, goodness, good in working for the shake of nation. In the book of izhah Al-Nasyiin, Sheikh Mustafa Al-Ghalayaini gives advice and encouragement to teenagers to become the main person. He hopes that moral education is embedded in the souls of teenagers so that they can shape the personality of teenagers who have good morals in accordance with the guidance of the Qur'an and hadith